An excess of active galactic Nnuclei triggered by galaxy mergers in MaNGA galaxies of stellar mass ∼1011M⊙ - Comerford, Julia M.; Nevin, Rebecca; Negus, James; Barrows, R. Scott; Eracleous, Michael; Müller-Sánchez, Francisco; Roy, Namrata; Stemo, Aaron; Storchi-Bergmann, Thaisa; Wylezalek, Dominika (The astrophysical journal, 2024)
To facilitate new studies of galaxy-merger-driven fueling of active galactic nuclei (AGNs), we present a catalog of 387 AGNs that we have identified in the final population of over 10,000 z < 0.15 galaxies observed by the Sloan Digital Sky Survey-IV (SDSS-IV) integral field spectroscopy survey Mapping Nearby Galaxies at Apache Point Observatory (MaNGA). We selected the AGNs via mid-infrared Wide-field Infrared Survey Explorer colors, Swift/Burst Alert Telescope ultra-hard X-ray detections, NRAO Very Large Array Sky Survey and Faint Images of the Radio Sky at Twenty centimeters radio observations, and broad emission lines in SDSS spectra. By combining the MaNGA AGN catalog with a new SDSS catalog of galaxy mergers that were identified based on a suite of hydrodynamical simulations of merging galaxies, we study the link between galaxy mergers and nuclear activity for AGNs above a limiting bolometric luminosity of 1044.4 erg s−1. We find an excess of AGNs in mergers, relative to nonmergers, for galaxies with stellar mass ∼1011 M ⊙, where the AGN excess is somewhat stronger in major mergers than in minor mergers. Further, when we combine minor and major mergers and sort by merger stage, we find that the highest AGN excess occurs in post-coalescence mergers in the highest-mass galaxies. However, we find no evidence of a correlation between galaxy mergers and AGN luminosity or accretion rate. In summary, while galaxy mergers overall do appear to trigger or enhance AGN activity more than nonmergers, they do not seem to induce higher levels of accretion or higher luminosities. We provide the MaNGA AGN Catalog and the MaNGA Galaxy Merger Catalog for the community here.
Im Titel ist 11 hochgestellt
Gesehen am 20.08.2024